Impact of Thin Endometrium in Frozen Embryo Transfer: Thesis Summary Article - A, Sakthi (Clinical Journal of Obstetrics and Gynecology, 2025)
Background: Endometrial Thickness (EMT) is considered an important prognostic factor in assisted reproductive technology (ART), particularly in frozen embryo transfer (FET) cycles. Thin endometrium (< 7 mm) is often associated with implantation failure and reduced pregnancy rates, although its precise impact remains controversial. Objective: This thesis summary evaluates the role of thin endometrium in FET cycles, discusses etiologies, diagnostic modalities, treatment approaches, and reviews available patient data. Methods: We retrospectively analyzed 69 patients who underwent FET at Saveetha Medical College. Endometrial thickness was assessed via transvaginal ultrasound. Various treatment strategies including hormonal therapies (estradiol, progesterone), vasoactive agents, granulocyte colony-stimulating factor (G-CSF), platelet-rich plasma (PRP), L-arginine, sildenafil citrate, vitamin E, pentoxifylline, and stem cell therapy were reviewed for their efficacy in improving endometrial receptivity. Results: Endometrial thickness < 7 mm correlated with lower pregnancy rates compared to patients with thickness ≥ 7 mm. Hormonal and adjuvant therapies reported varying degrees of success in improving EMT and subsequent pregnancy outcomes. Vascularity, angiogenesis, and Doppler studies also demonstrated a significant association with endometrial receptivity. Conclusion: Thin endometrium remains a critical challenge in ART cycles. Multimodal therapeutic approaches may improve outcomes; however, larger prospective studies are required to establish standardized protocols. Our patient data support that even minimal increases in EMT can enhance implantation success.